Survival in Duchenne muscular dystrophy - RALL, SUSANNE (Pacini Editore SpA, 2012)
OBJECTIVE: To determine the survival in a population of German patients with Duchenne muscular dystrophy. PATIENTS AND METHODS: Information about 94 patients born between 1970 and 1980 was obtained by telephone interviews and questionnaires. In addition to age of death or actual age during the investigation, data concerning clinical course and medical interventions were collected. RESULTS: 67 patients with molecularly confirmed diagnoses had a median survival of 24.0 years. Patients without molecular confirmation (clinical diagnosis only) had a chance of 67 % to reach that age. Grouping of our patient cohort according to the year of death (before and after 2000), ventilation was recognized as main intervention affecting survival with ventilated reaching a median survival of 27.0 years. For those without ventilation it was 19.0 years. CONCLUSION AND CLINICAL RELEVANCE: our study provides survival data for a cohort of DMD patients in Germany stratified by year of death. Median survival was 24.0 years in patients confirmed by molecular testing. Ventilated patients had a median survival of 27 years. We consider this piece of information helpful in the medical care of DMD patients.